A prelude to the Studia Anglica Posnaniensia special issue “America and deep time: alternate temporalities, geographies, and histories” - Ambroży, Paulina; Macedulska, Katarzyna; Olsza, Małgorzata; Wilczyńska, Elżbieta (Studia Anglica Posnaniensia, 2025)
No abstract.